The Power of Literature: Philosophy Beyond Authorial Aims - Kalášková, Diana (Univerzita Pardubice, 2024)
The distinction between literature and philosophy can be articulated in various ways. One of the central issues of this distinction revolves around the nature of argumentation. While literature engages with fictional people and events, philosophical claims require rational justification. Thus, it is easy to assume that argumentation is something that concerns philosophy, but not literature. This thesis proposes a broader understanding of argumentation, building upon Cora Diamond's suggestion that literature has a power akin to philosophical argumentation. Even if literature does not conform to the rigid requirements of rational argumentation prevalent in contemporary academic philosophy, I argue that literature demonstrates a capacity for argumentation. This capacity, however, does not entail extracting explicit argumentative structures from narratives. Rather, the argumentative power of literature is discerned through its ability to illuminate overlooked moral aspects of reality. By viewing literature as a form of argumentation in a broader sense, I assert that its argumentative power is inherent to the text, i.e. independent of the authors' presumed intent to convince their readers. Focusing on this inherent power reveals an intersection between literature and philosophy, underscoring the relevance of literature to moral philosophy. In the latter part of this thesis, I conduct close readings of two novels - Elizabeth Costello by Coetzee and Kaputt by Malaparte - to illustrate how this broader conception of argumentation manifests in concrete cases. Both novels illuminate the intimate connection between narratives and meaning-making, elucidating how the traumas we encounter can shape the stories we construct, our understanding of ourselves, and the world.
Keywords: philosophy and literature; Cora Diamond; argumentation; difficulty of reality; literature and morality; Elizabeth Costello; Kaputt; filosofie a literatura; Cora Diamond; argumentace; složitost skutečnosti; literatura a morálka; Elizabeth Costello; Kaput